ANALISIS EFISIENSI DAN EFEKTIVITAS ANGGARAN BELANJA PADA BADAN PERENCANAAN PEMBANGUNAN RISET DAN INOVASI DAERAH SIMALUNGUN - Silalahi, Risda Wati; Sembiring, Sabeth; Parhusip, Poltak Teodorus (Jurnal Ilmiah Akuntansi (JIMAT), 2025)
This research aims to analyze the efficiency and effectiveness of the shopping budget at the Office of the Regional Planning, Research, and Innovation Agency of Simalungun based on measurements of effectiveness and efficiency. The population in this study consists of all data from the Budget Realization Report at the Office of the Regional Planning, Research, and Innovation Agency of Simalungun. The sample in this study is the Budget Expenditure Realization Report from the Office of the Regional Planning and Research and Innovation Agency of Simalungun for the years 2019-2023. The data collection techniques in this study involve interviews and documentation. The data analysis technique used is descriptive data analysis. The level of efficiency of budget realization in BAPPERIDA Simalungun Regency in the last five years from 2019-2023 is very efficient. The utilization and use of the budget for the implementation of programs/activities at the Simalungun Regional Development Planning, Research and Innovation Agency has been very efficient in realizing it. This is because BAPPERIDA Simalungun has almost no indirect spending other than employee salaries and benefits. The level of effectiveness of the realization of the budget in BAPPERIDA Simalungun Regency was not effective in 2019 and 2021 because there were still programs that had not been implemented and realized. Then in 2022 it is in the less effective category because of the large difference between the budgeted costs and the realized ones used. Then in 2020 and 2023 it is in the effective category. This is because BAPPERIDA Simalungun has almost no indirect spending other than employee salaries and benefits. Suggestions for the BAPPERIDA Simalungun Office to maximize the use of the budget provided by adding existing programs and activities and minimizing factors that hinder the performance of BAPPERIDA itself. Suggestions for the BAPPERIDA Simalungun Office to maximize the use of the budget provided by adding existing programs and activities and minimizing factors that hinder the performance of BAPPERIDA itself.